An on-chip soft-start pseudo-current hysteresis-controlled buck converter for automotive applications - Boutaghlaline, Anas; El Khadiri, Karim; Tahiri, Ahmed (Institute of Advanced Engineering and Science, 2024)
This paper introduces a novel direct current to direct current (DC-DC) buck converter that uses a pseudo-current hysteresis controller and an on-chip soft start circuit for improved transient performance in automotive applications. The proposed converter, implemented with Taiwan semiconductor manufacturing company (TSMC) 0.18 µm complementary metal oxide semiconductor (CMOS) one-poly-six-metal (1P6M) technology, includes a rail-to-rail current detection circuit and an on-chip soft start circuit to handle transient responses and improve efficiency. Transient response analysis shows fast settling times of 28 µs for both load current changes from 100 mA to 1 A and reversals with consistent transient voltages of approximately 190 mV and peak power efficiency of 99.32% at 5 V output voltage and 100 mA load current. Additionally, the converter maintains a constant output voltage of approximately 5 V across the entire load current range with an average accuracy of 90.41%. A comparative analysis with previous work shows superior performance in terms of figure of merit (FOM). Overall, the proposed pseudo-current hysteresis controlled buck converter exhibits remarkable transient response, load regulation and power efficiency, positioning it as a promising solution for demanding applications, particularly in automotive systems where precise voltage regulation is crucial.